La naturaleza como sujeto de derechos en el constitucionalismo ecuatoriano - Albuja, Ángel J. (2020)
This interesting investigation is focused on the rights of nature from the point of view in which it is intended to give nature the perspective of a legal entity so that it can make its rights prevail, but what is not determined is that being eventually a legal person, who would represent him in a possible defense of his rights against any violation thereof, and how this representative would make the enjoyment of nature's rights effective, the attempt try to protect it directly collides with an economic system worldwide that is established and related to the full use of natural resources, before a society focused on increasing its economy, for this fact, there is an excessive exploitation of natural resources, mostly non-renewable. Thus, being outstanding in Latin America and worldwide, that the Constitution of the Republic of Ecuador of 2008 standing out with the implementation and constitutional acknowledgement of the rights of nature, and its categorization as a subject, which consequently gives to nature an equal rank to the human being. From this point, Ecuador has become a worldwide benchmark in establishing constitutional guarantees that are of immediate compliance and application; what other countries are trying to implement this nature protection initiative; in this way to inaugurate within a constitutionalism clearly concerned with the human being, the protection of a non-human entity, with the representation of those who obtain resources from it, directing a conscious and adequate use of what nature provides, taking care of this, including their life cycles.